1977
DOI: 10.2514/3.47947
|View full text |Cite
|
Sign up to set email alerts
|

Subsonic MHD-diffuser performance with high blockage

Abstract: Diffuser performance with high blockages is analyzed by a two-dimensional turbulent-flow model. This model is used to analyze the performance of simple two-dimensional, plane-walled diffusers and also of threedimensional diffusers up to and beyond the blockage limits for which previous analytical or experimental data are available. The effects of important design parameters on diffuser performance are investigated. The parameters considered are the blockage, divergence angle, Mach number, aspect ratio, and wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…31 ' 32 An estimate of the reduction in pressure recovery of simple twodimensional, plane-walled diffusers was given by Doss. 31 It was shown that the pressure recovery decreases from C PR = 0.7 at zero blockage down to C PR =0.48 at 18% blockage. This indicates that the pressure recovery of diffusers for baseload linear generators, which operate with even higher inlet blockages, will probably be about C PR =0.4-0.45.…”
Section: Inlet Blockagementioning
confidence: 97%
“…31 ' 32 An estimate of the reduction in pressure recovery of simple twodimensional, plane-walled diffusers was given by Doss. 31 It was shown that the pressure recovery decreases from C PR = 0.7 at zero blockage down to C PR =0.48 at 18% blockage. This indicates that the pressure recovery of diffusers for baseload linear generators, which operate with even higher inlet blockages, will probably be about C PR =0.4-0.45.…”
Section: Inlet Blockagementioning
confidence: 97%